Making Japanese Language Learning Models through Multimedia-Based SCL Implementation - Ariani Tanjung (Politeknik Negeri Padang, 2018)
This research is an action research, design in action research designed to looking fo solution to improve japanese teaching process. According to Karwono (2012). The Implementation of action research starting with awareness of the disturbing problem and cause prevent the achievment of education purpose an give dab impact from process and student grade when learning process aplied. Due to those problem then we set the focus of the problem more detail by collecting systematic data with relevan literature review. Things that must be considered is input, process, and output. If in learning process we find incomptability with education purpose or Curiculum then the process must be fixed for education goals, and especially vocational education system. Therefore I try to make a design in the form ofStudent centered learning based on multi media. For technology media using Flash MX, adobe premier, and adobe photoshop program